Development of Learning Materials Based on Student Book to Improve Vocabulary of Elementary School Students - Ngguna, Apriwati Mura; Suryantini, Made Detri; Isyarotullatifah, Isyarotullatifah (Riwayat: Educational Journal of History and Humanities, 2025)
This study aimed to develop effective vocabulary learning materials for second-grade students at an elementary school using the ADDIE instructional design model. The development process followed the five stages of ADDIE: Analysis, Design, Development, Implementation, and Evaluation. This Research and Development (RD) study focused on identifying students' needs in vocabulary acquisition and addressing the challenges observed in existing materials. The analysis phase identified low engagement, poor retention, and lack of contextual understanding among students. Based on these findings, the materials were designed to be interactive, visually engaging, and contextually relevant. Two units were developed: "The Elephant Is Big" and "The Giraffe Is Tall." The materials were implemented in a classroom setting and evaluated through pre- and post-tests, as well as expert validation. The results showed a significant improvement in vocabulary mastery among students, along with positive feedback from teachers and learners. This study concludes that the ADDIE model is a practical framework for developing instructional materials tailored to young learners needs in vocabulary acquisition.